Survey of ICT and Education in Africa : Democratic Republic of Congo Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. ICT remains largely undeveloped in the Democratic Republic of Congo (DRC). This is largely because the country is still unlinked to the SAT3 underwater optical fiber cable and is thus forced to rely entirely on expensive and unstable satellite connectivity. The lack of a national policy for ICT development, and the apparent lack of concern for the subject among government officials, is not helpful. However, largely through the work of non-governmental actors, and Law 012/2002, ICT applications are slowly emerging. Greater support from government is needed to ensure that these initiatives are expanded to improve the country's currently low levels of school participation and to reduce the major digital gaps which currently separate the north and south, urban and rural areas, and male and female populations in the DRC.